Avtobiografski diskurz Teorija in praksa avtobiografije v literarni vedi, humanistiki in družboslovju - Koron, Alenka; Leben, Andrej (Studia litteraria, 2011)
This collective volume is the first monographic and interdisciplinary study of autobiography in Slovenia. Nineteen authors are discussing the issues of its development, combining the methods of literary scholarship with the philosophical, historiographical, ethnological, sociological and other perspectives. Theoretical insights are complemented by a series of case studies on the history of autobiographical discourse in Slovenian cultural space and beyond it from the end of the 18th century to the present.